Efficacy and safety of long fusion versus short fusion in degenerative scoliosis: a systematic review and meta-analysis - Bin Zheng; Qiang Zhou; Xuanwen Liu; Zhe Qiang (Journal of Orthopaedic Surgery and Research)
Abstract Background This study aimed to evaluate the efficacy and safety of long fusion versus short fusion in patients with degenerative scoliosis. Methods Databases were systematically searched up to June 2024. The authors applied Review Manager 5.4 to manage the data and perform the analysis. Results After the selection of 611 studies from electronic databases, 13 studies were eligible for inclusion. These 13 studies included 1261 patients: 534 patients underwent long fusion, and 727 underwent short fusion. At baseline, the Cobb angle, coronal imbalance, and sagittal imbalance were greater in the long fusion group. There was no difference in the VAS back, Cobb angle, ODI, hospital stay, revision surgery, adjacent segment degeneration, sacral slope, pelvic tilt, Cobb angle, lumbar lordosis, coronal balance, or sagittal balance at the final follow-up. The surgery time, complication rates, and amount of blood loss were greater in the long fusion group. Conclusions Long fusion leads to superior radiographic improvement, particularly in reducing the Cobb angle and reconstructing coronal and sagittal balance. The long fusion group was inferior in terms of increased surgical time, more blood loss, and higher postoperative complication rates. At the final follow-up, there was no difference in the clinical or radiographic outcomes between the long and short groups. For patients with a large coronal Cobb angle and significant coronal or sagittal imbalance, long fusion surgery should be performed. On the other hand, for patients whose milder deformities and clinical symptoms are the main concern, short fusion surgery is recommended.